Morfologia da planta, inflorescência, fruto, semente e plântula de nandina domestica thunb - Perotti, Adriano Antônio (2007)
The work aimed to describe and to illustrate morphologic aspects of the plant, inflorescence, fruit, seed and seedling of Nandina domestica Thunb. In the accomplished tests, were evaluated twenty head offices installed in the production area of the Floricultura Oeste Ltda, in the metropolitan area of Cascavel - PR. Were observed in the plants the following aspects: root, stem and leaves. In the inflorescences were described: the kind, color and the reproductive structures. In the fruits, the following aspects were observed: color, mass and diameter. In the seeds, were verified forms, size and mass. In the seedling, were observed the protrusion of the primary root, hipocótilo, epicotyls, plúmula and cotyledons. The observations were accomplished with aid of table magnifying glass and the measures were taken with digital pachymeter. The flower is diclamídea, with superior ovary, the fruit is an impermeable red berry, containing two seeds, which possess elliptic format, with homócromo embryo and epigeous germination.